THEME ANALYSIS AS A TOOL TO TEACH COHESIVE ENGLISH TEXTS - Budi Rahayu (Journal of Education Papua Baru, 2022)
The fact shows that teaching writing English as a foreign language in Indoneia is not easy. The students’ problems seem to be related to grammar, vocabulary, genre and mostly cohesion. We should always find appropriate better ways to solve this problem. One of the ways to solve this problem may be the application of Systemic Fumctional Linguistics, especially the use of Theme in shaping a cohesive text. It is shaped by making the Theme of the clause be related with the Theme or the Rheme of the previous clauses.Keywords: Theme, Rheme, Clause, Cohesion